2020
DOI: 10.1101/2020.02.19.20024885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative study of the lymphocyte change between COVID-19 and non-COVID-19 pneumonia cases suggesting uncontrolled inflammation might not be the main reason of tissue injury

Abstract: Background: The corona virus disease 2019 (COVID-19) shows unusually high transmission rate and unique clinical characteristics, with key pathological mechanism remaining unclear. Here, we analysed the laboratory data based on clinical samples from COVID-19 patients, in parallel comparison with non-COVID-19 pneumonia cases, in an attempt to elucidate the key pathological features of COVID-19 during its infection of the human body. Methods: We analysed biochemical indices and lymphocyte subpopulation in COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…The significant of laboratory examinations was blood routine, the results suggested leukocytes were mainly normal or decreased, and lymphocytes reduced evidently in many COVID-19 patients [13] . A recent research indicated that lymphocytes,especially CD3 + lymphocytes and CD45 + lymphocytes, decreased significantly in comparison with non-COVID patients, while there was no significantly difference in quantities and proportions of neutrophils and monocytes [14] .Results of this analysis showed lymphocytes and eostinophils decreased obviously without leukocytes increasing in most patients, and neutrophils,monocytes and platelet mainly kept at normal range,it was consistent with previous reports. In term of chest CT, the typical image features were peripheral, subpleural ground glass opacities in the lower lobes.…”
Section: Discussionsupporting
confidence: 91%
“…The significant of laboratory examinations was blood routine, the results suggested leukocytes were mainly normal or decreased, and lymphocytes reduced evidently in many COVID-19 patients [13] . A recent research indicated that lymphocytes,especially CD3 + lymphocytes and CD45 + lymphocytes, decreased significantly in comparison with non-COVID patients, while there was no significantly difference in quantities and proportions of neutrophils and monocytes [14] .Results of this analysis showed lymphocytes and eostinophils decreased obviously without leukocytes increasing in most patients, and neutrophils,monocytes and platelet mainly kept at normal range,it was consistent with previous reports. In term of chest CT, the typical image features were peripheral, subpleural ground glass opacities in the lower lobes.…”
Section: Discussionsupporting
confidence: 91%
“…However, some CoVs are thought to induce T-cell apoptosis by the activation of apoptosis pathways [73], while depletion of CD4+ cells in later stages is associated with immune-mediated interstitial pneumonitis and delayed clearance of pathogen [74]. In SARS-CoV-2 infected patients, both the counts of CD4 + cells and CD8+ cells in severe pneumonia patients were lower than non-severe patients [75]. Similar results were observed in SARS-CoV infected patients [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed RNA-seq data of PBMC samples from three male individuals infected with SARS-CoV-2 and three control individuals without SARS-CoV-2 infection obtained from China (Supplemental Table 1) [20]. We first sought to confirm the observed immunological changes observed during COVID-19 disease in peripheral blood by others [15,[21][22][23][24]. We utilized the bulk transcriptome PBMC data and estimated the abundances of 22 immune cell types using the CIBERSORT analytical deconvolution tool [25].…”
Section: Sars-cov-2-infectionmentioning
confidence: 99%